Methods of factor effects diagnosis in the business processes of alternative energy enterprises - Климчук, Марина Миколаївна (Technology audit and production reserves, 2013)
The economic realities of the dominant ways of society development determine the ontogenesis of alternative energy companies, the successful activity of which depends on the effective management of business processes, with the indicator being modern methodological approaches to their diagnosis. Today, there are a lot of publications concerning this problem, but the diagnosis of factor effects underexplored. The article presents theoretical and methodological approach to the evaluation of factor effect the first ever worked out in the context of management efficiency of the business processes at the alternative energy companies, which allows to identify the dominant internal and external components that affect the efficiency of the production and economic system. This methodological approach is developed on the basis of the method of pair comparisons of multidimensional scale of T. Saaty. As a result, a matrix of pair comparisons was formulated and the primary number of factors of external and internal environment was interpreted, which allowed the administration of alternative energy companies to identify the dominant components of the effects in order to identify variables that ensure efficient operation of industrial and economic system in today’s economic realities and make effective managerial decisions of the enterprise alternative energy.